THE PROBLEM OF INTELLECTUAL CULTURE IN DIFFERENT HISTORICAL CONTEXTS (Scientific journal of the Fergana State University, 2024)
This article examines the socio-philosophical nature of the concept of intelligence in the context of different historical periods, the importance of intellectual property in the economic development of modern society, as well as the modern need for the development of intellectual culture. Based on the methods of comparative analysis and historicity, interperiod approaches to the concept of intelligence are analyzed based on the works of CIS researchers.